1985
DOI: 10.1007/bf01982879
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rat andβ-human interferons on hyperacute experimental allergic encephalomyelitis in rats

Abstract: Human interferon-beta (human IFN-beta) and rat interferon (rat IFN) were evaluated on experimental allergic encephalomyelitis (EAE) in rats, a delayed cellular reaction resembling human multiple sclerosis (MS). Rat IFN was active by intravenous and intracerebroventricular routes. It decreased the severity of clinical symptoms of paralysis during the 22 days of the assay. Human IFN-beta, on the contrary, had no effect when similarly tested in this rat model. Cyclophosphamide delayed the onset of paralysis, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Because nonmethylated B 12 was not effective, the results observed involved biological methylation. Many, but not all, immunological IFN-␤ effects are species specific (34). When hIFN-␤ was used in a similar set of experiments, there was a significant effect of the combination treatment, suggesting that the biological effects relevant in this study were not strictly species specific (data not shown).…”
Section: Combination Therapy Attenuates Nonautoimmune Demyelinationmentioning
confidence: 78%
“…Because nonmethylated B 12 was not effective, the results observed involved biological methylation. Many, but not all, immunological IFN-␤ effects are species specific (34). When hIFN-␤ was used in a similar set of experiments, there was a significant effect of the combination treatment, suggesting that the biological effects relevant in this study were not strictly species specific (data not shown).…”
Section: Combination Therapy Attenuates Nonautoimmune Demyelinationmentioning
confidence: 78%
“…As discussed above, GA a random copolymer of tyrosine, glutamate, alanine and lysine in ratios resembling myelin basic protein. (Abreu, 1982;Jacobs et al, 1982;Hertz and Deghenghi, 1985;Abreu et al, 1986;Paty and Li, 1993; Brod and Burns, 1994;Ruuls et al, 1996;Yu et al, 1996; Croxford et al, 1998b;van der Meide et al, 1998;Luca et al, 1999;Yasuda et al, 1999;Wender et al, 2001;Schaefer et al, 2006;Jaini et al, 2006;Martin-Saavedra et al, 2007) Other drugs et al, 1971;1973;1974;2004; Keith et al, 1979;Lisak et al, 1983; Aharoni et al, 1993;1997;Johnson et al, 1995;Gran et al, 2000; Gilgun-Sherki et al, 2003;Illes et al, 2004;Stern et al, 2004; Giuliani et al, 2005a,b of the immunogenicity of proteins. GA was developed initially as a putative encephalitogen; however, it showed ...…”
mentioning
confidence: 99%
“…would be contributing to the increased variance. As far as we know, our findings are the first demonstration that human r-IFN β-1b is efficacious in an animal EAE model, while it failed to suppress in the rat EAE model in contrast to rat IFN β effective (Hertz & Deghenghi, 1985). Since mononuclear cells were markedly less infiltrated into the brain parenchyma by chronic treatment with GPA-Betaferon (preliminary data), it is conceivable that the antigen specific T-cells and activated macrophages are suppressed for their migration into the brain in association with BBB damage (Swanborg, 1995).…”
Section: Discussionmentioning
confidence: 61%
“…An immune-mediated attack on the oligodendrocytes that synthesize MBP is made by the Th 1 cells and the tissue macrophages/microglias that become activated through Th 1 cell cytokine action, mediating demyelination (Cantorna et al, 1996). The onset of clinical signs in the guinea pig model appears in a similar period of time for rats and mice; 6-12 days, [6-7 days reported by Hertz and Deghenghi (1985), 9-12 days by van der Meide et al (1998) and 10 days by Cantorna et al (1996)] after immunization. Hind limbs paralysis was also defined as a major sign in the rodent's model as well.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation